Study of the dynamics of сhanges in the structure of plain weave fabrics in the formation process - Федорченко, Олена Вікторівна; Закора, Оксана Василівна; Рязанова, Олена Юріївна (Eastern-European Journal of Enterprise Technologies, 2015)
Experimental studies of the structure of plain weave fabrics to predict the real structure and properties were carried out in the paper. To this end, dynamic processes of changes in the structure of fabrics at the stages of manufacturing: in the design, in threading on the loom and after removal from the loom at steady state were analyzed. The order of the phase structure, as a characteristic of mutual spatial orientation of the systems of warp and weft threads in the fabric, was selected as a criterion. To determine the structure phase of fabrics, the method of micro-sections, whose images were processed using a special computer program was applied. Analysis of the data showed that the order of the phase structure of the fabric increases during the transition from one fabric formation stage to another, but the nature of these changes is ambiguous and depends on the ratio of diameters and bending waves of threads taking into account their mutual position. Defining the patterns of these changes for plain weave fabrics will allow to improve the design methods of fabrics of other weaves.